Morfodinâmica de sistemas eólicos costeiros: Um modelo baseado em exemplos do Holocénico brasileiro e seu potencial interpretativo - Giannini, P. C.F.; Sawakuchi, A. O.; Mendes, V. R.; Zular, A.; Andrade, H. A.A.; Martinho, C. T.; Guedes, C. C.F.; Nascimento, D. R.; Tanaka, A. P.B.; Fornari, M. [UNESP] (My University, 2014)
The morphodynamics of coastal aeolian systems is controlled by the relative sedimentary balance, i.e., the ratio between absolute sediment balance (influx-efflux) and accumulation space. The accumulation space depends on source area extension as well as on the equilibrium (sand saturation) dimensions: the distance along wind direction (Deq) and the height (Heq) in which the balance influxefflux keeps positive. The morphologic elements identified in the Brazilian+ coastal aeolian systems are organized in three associations: beach-dune (foredunes, protodunes and sand sheets); deflation plain (blowouts, trailing ridges, gegenwalle and parabolic dunes); and dune field (barchans and barchanoid chains, with the role of raise the accumulation until Heq, and precipitation ridges and depositional lobes, whose function is to deposit sand until Deq). The Brazilian coastal aeolian systems can be divided in four categories as for the element associations involved in the energy/supply equilibrium. This equilibrium can be satisfied in the beach-dune association, in the relation between beach-dune and deflation plain associations, in the relation among beach-dune, deflation plain and dune field associations or in the direct passage from beach-dune to dune field. Detailing these four categories, eight morphodynamic types of aeolian systems are proposed in this work, numbered from 1 to 8 in crescent order of relative sedimentary budget. When submitted to disequilibrium near equilibrium, the aeolian system responds in the opposite direction to the perturbation, in a typical negative feedback or self-regulation reaction. When the perturbation is far from the equilibrium, the aeolian system response is a positive feedback or self-organization, that consists in the instantaneous transformation from a morphodynamic stage to other in which the sand retention is minor if the relative sedimentary balance have fallen, or major if the relative sedimentary balance have risen.
Morphodynamics of coastal aeolian systems: A model based on Holocene brazilian examples and its interpretative potential
Keywords: Aeolian coastal system; Aeolian morphodynamics; Classification of dunes; Holocene; Systems theory